'An extremely dangerous book'? James Hope Moulton's Religions and Religion (1913). (2015) - Wellings, Martin
Abstract : On 4 April 1917 the British steamship SS City of Paris was torpedoed by a German submarine in the Gulf of Lions, and sank with considerable loss of life. Among the passengers was the Wesleyan Methodist scholar James Hope Moulton.' Paying tribute to his friend and colleague, Arthur Samuel Peake recorded the 'tragic irony' of the death under such circumstances of an eloquent advocate of peace and of a scholar whose international reputation in New Testament studies was signalled by plaudits from Harnack, a doctorate from the University of Berlin and a longstanding academic friendship with Adolf Deissmann. Moulton, however, was more than a New Testament scholar. His presence in the Mediterranean in the spring of 1917 came about through his expertise in the history and thought of Zoroastrianism, which had taken him to India for eighteen months' work with the Parsee community under the auspices of the Indian YMCA.